Pengaruh Media Audio Visual pada Pendidikan Kesehatan untuk Pencegahan Stroke pada Penderita Diabetes di Puskesmas Tekarang - Erni Juniartati; Sarliana Zaini; Marsia Marsia (Jurnal Ners, 2025)
Diabetes Mellitus is a metabolic disorder of carbohydrates, fats, and proteins caused by abnormalities in insulin secretion, insulin action, or both. Diabetes Mellitus is known as a silent killer because it often goes unnoticed until complications arise. This study aimed to prove the significant influence of knowledge and attitudes of diabetes mellitus patients before and after being given an intervention in the form of health education through educational videos about stroke prevention. The method used is a quasi-experimental design with a pretest-posttest with control group. The intervention group received education through video media, while the control group was given education with leaflet media. The results showed a significant effect of audio-visual media on knowledge with a p-value of 0.012 (p < 0.05). The average knowledge difference in the intervention group was 22.35, while in the control group it was 15.67. The effect on attitude was also significant with a p-value of 0.001 (p < 0.05). The average attitude difference in the intervention group was 24.84, while in the control group it was 15.88. The conclusion of this study is that health education through audio-visual media significantly influences the knowledge and attitudes of diabetes mellitus patients in stroke prevention.